Phytochemical Screening, Antimicrobial and Antioxidant Activities of Selected Mangrove Species - Dahibhate, Nilesh L.; Roy, Utpal; Kumar, Kundan (Current Bioactive Compounds, 2020)
Background: Mangrove plant extracts are used in folkloric medicine as aphrodisiac, sedative, antioxidant, antimicrobial and antimalarial. Screening for antimicrobial, phytochemical and antioxidant activities of fourteen mangroves plant species (Aegiceras corniculatum, Acanthus ilicifolius, Avicennia alba, Avicennia marina, Avicennia officinalis, Bruguiera cylindrica, Bruguiera gymnorhiza, Ceriops tagel, Excoecaria agallocha, Kandelia candel, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, and Sonneratia caseolaris) in various solvents are reported in this work. Methods: The antimicrobial screening was carried out using agar well diffusion method. In this study, nine pathogenic strains were used, including three Gram-positive and six Gram-negative bacteria. Phytochemical screening, total flavonoids, total phenolic and antioxidant activity was tested by DPPH radical scavenging assay. Four phenolic compounds (gallic acid, vanillin, tannic acid and quercetin) were quantified by LC-MS/MS in selected mangrove species. Results: Antimicrobial screening showed Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis and Pseudomonas aeruginosa were most susceptible to ethyl acetate extract as compared to ethanol and methanol extract. Ethyl acetate extract of Avicennia marina and Bruguiera gymnorhiza showed strong antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis and Pseudomonas aeruginosa. Phytochemical analysis revealed the presence of saponins, phenolics, flavonoids, alkaloids, tannins, and terpenoids, which was found to be variable as per the solvent used for extraction. In addition, total phenolics and total flavonoids content with different solvents were found in the range of 11.08 to 196.76 mg GAE/g and 12.92 to 110.3 mg QE/g of extract respectively. Moreover, antioxidant capacities expressed in terms of IC50 (mg/mL) showed that methanol extract exhibited higher antioxidant capacity followed by ethanol extract. LC-MS/MS analysis showed gallic acid and tannic acid are present in higher concentration in Aegiceras corniculatum and Sonneratia caseolaris than other species. The vanillin and quercetin were found in the least concentration. Conclusion: Mangroves species are rich source of antioxidant, phenolics and antimicrobial compounds.
Keywords: microorganism